Association of Dyslipidemia with Chronic Kidney Disease in Patients Requiring Renal Replacement Therapy - Ansar, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To highlight the association of dyslipidemia in patients of Chronic Kidney Disease requiring Hemodialysis (CKD-5D) at a tertiary care hospital. Study Design: Comparative cross-sectional study Place and Study of Duration: Department of Nephrology, Combined Military Hospital, Kharian, Pakistan, Jan to Jun 2023. Methodology: Using consecutive sampling, CKD patients of either gender with age > 20 years, both dialysis dependent (CKD-5D) and non-dialysis (CKD-5ND) were included and divided into two Groups of 50 patients each. Serum cholesterol, triglycerides (TGs), low-density lipoprotein (LDL), and high-density lipoprotein (HDL) levels in both Group patients were assessed and analyzed. Measures of association like odds ratio and prevalence ratio were calculated. Results: Diabetes Mellitus was the most common cause of CKD in both groups. Majority of Group A patients 20(40.0%) had CKD-5 for 3-5 years as compared to majority of Group B patients 22(44.0%) who had CKD-5 for > 5 years with dialysis dependency for at-least 1 year (p=0.805). LDL-C levels comparison in both groups showed hyper-LDL-cholesterolemia in 30(60.0%) vs 37(74.0%) of Group A (CKD-5ND) and Group B (CKD-5D) patients, respectively (p=0.109). Odds ratio (OR) and prevalence ratio (PR) were > 1 indicating there were higher odds and higher prevalence of raised LDL levels in CKD-5D (OR=1.89 [95% CI 0.812 - 4.431], p=0.069, PR = 1.23). Conclusion: There is high prevalence of dyslipidemia in advancing CKD patients and with declining eGFR dyslipidemia risk increases leading to increased incidence of fatal events.